2004
DOI: 10.1103/physrevb.70.115111
|View full text |Cite
|
Sign up to set email alerts
|

Electric field gradient calculations forLixTiS2and comparison withLi

Abstract: The elements of the electric field gradient tensor at Li position in the intercalation compound Li x TiS 2 (with x = 0.25, 0.33, 0.67, and 1.0) were calculated with first-principles methods and periodic supercell models. The theoretical results obtained with density functional and Hartree-Fock hybrid methods were compared with experimental field gradients extracted from 7 Li NMR spectra from the literature and from our measurements presented here. The dependence of calculated field gradients on the basis set a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 55 publications
6
89
0
Order By: Relevance
“…[3,43] The efficiency of the EFG calculations has been demonstrated for a large series of nuclei. [44][45][46][47] Nevertheless, when considering a second-order magnetic response as the shielding tensor, intricacies appears. It was demonstrated that the PAW approach does not preserve the translational invariance of eigenvectors in the presence of a uniform magnetic field.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[3,43] The efficiency of the EFG calculations has been demonstrated for a large series of nuclei. [44][45][46][47] Nevertheless, when considering a second-order magnetic response as the shielding tensor, intricacies appears. It was demonstrated that the PAW approach does not preserve the translational invariance of eigenvectors in the presence of a uniform magnetic field.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The electronic structure calculations have been performed using the linear combination of atomic orbitals method as implemented in CRYSTAL first-principles code. [73] We used localized Gaussian-type basis sets including polarization orbitals and considered all the electrons for Ti [74], O [75], V [78], K and Nb [76], F and Co [77]. The Hartree-Fock pseudopotential for Sr [75], and the Stuttgart energy-consistent pseudopotential for La [79] were used.…”
Section: Technical Detailsmentioning
confidence: 99%
“…Calculations were performed using the linear-combination of atomic orbitals method implemented in the CRYSTAL code 35 . We used localized Gaussian-type basis sets including polarization orbitals and considered all the electrons for Ti 36 , O 37 and Al 38 . For Sr, we used a HartreeFock pseudopotential 37 .…”
Section: First-principles Calculationsmentioning
confidence: 99%